2020
DOI: 10.3390/en13215554
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Hybrid Cooling of the Flame Tube in a Small Triple-Swirler Combustor

Abstract: An experimental and numerical investigation is conducted to study the influence of different cooling schemes on the wall temperature of the flame tube in a small triple-swirler combustor in this paper. Two different cooling structures are adopted: the impingement-film and inclined multi-hole cooling structure (Scheme B, C), and the inclined multi-hole control group (Scheme A). The impact of parameters including inlet temperature (373–423 K), inlet Mach number (Ma) (0.12–0.18), and fuel–air ratio (FAR) (0.02–0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…They compared their results in cases without outlets and found that the nozzle field with outlets had a 20-30% higher heat transfer rate. Zhang et al [28] compared the cooling performance of hybrid impingement cooling and effusion cooling of a multiswirler combustor and concluded that the hybrid impingement cooling method was very effective. Wu et al [29] investigated an array jet impingement cooling for a simulated chip using an additively manufactured manifold design that encloses the chip with working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…They compared their results in cases without outlets and found that the nozzle field with outlets had a 20-30% higher heat transfer rate. Zhang et al [28] compared the cooling performance of hybrid impingement cooling and effusion cooling of a multiswirler combustor and concluded that the hybrid impingement cooling method was very effective. Wu et al [29] investigated an array jet impingement cooling for a simulated chip using an additively manufactured manifold design that encloses the chip with working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Jet impingement cooling, ejecting high-velocity coolant from a nozzle or an orifice plate perpendicular to the target surface, yields a highly concentrated heat removal rate at the impact zone, which effectively cools a small area dissipating high heat flux. By utilizing both air and liquid as coolant, jet impingement cooling was studied in a variety of fields demanding dissipation of highly concentrated heat; cooling of blades in a gas turbine engine [11][12][13][14][15][16][17][18][19][20], quenching process in steel industries [21], and avionics cooling [22]. Jet impingement cooling is classified into three different configurations [23]: free jet when the jet is injected into less dense ambient fluid, submerged jet when the jet is injected into the same ambient fluid, and confined jet when the jet is injected into a confined space between the orifice plate and the target surface filled with the same fluid.…”
Section: Introductionmentioning
confidence: 99%